Sagot :
Answer:
The Solve by Factoring process will require four major steps:
Move all terms to one side of the equation, usually the left, using addition or subtraction.
Factor the equation completely.
Set each factor equal to zero, and solve.
List each solution from Step 3 as a solution to the original equation.
Step-by-step explanation:
Pa Follow Thanks
Answer:
- Move all terms to one side of the equation, usually the left, using addition or subtraction.
- Factor the equation completely.
- Set each factor equal to zero, and solve.
- List each solution from Step 3 as a solution to the original equation.
First Example
x2 + 3x = 8x - 6
Step 1
The first step is to move all terms to the left using addition and subtraction. First, we will subtract 8x from each side.
x2 + 3x - 8x = 8x - 8x - 6
x 2 - 5x = -6
Now, we will add 6 to each side.
x2 - 5x + 6 = -6 + 6
x 2 - 5x + 6 = 0
With all terms on the left side, we proceed to Step 2.
Step 2
We identify the left as a trinomial, and factor it accordingly:
(x - 2)(x - 3) = 0
We now have two factors, (x - 2) and (x - 3).
Step 3
We now set each factor equal to zero. The result is two subproblems:
x - 2 = 0
and
x - 3 = 0
Solving the first subproblem, x - 2 = 0, gives x = 2. Solving the second subproblem, x - 3 = 0, gives x = 3.
Step 4
The final step is to combine the two previous solutions, x = 2 and x = 3, into one solution for the original problem.
x2 + 3x = 8x - 6
x = 2, 3